A histopathological and genomics study of the mutated human FAM111B gene related POIKTMP disease - Tambwe, Nadine (Division of General Surgery, 2024)
Fibrosis is a pathological feature of many chronic inflammatory diseases, eventually leading to organ failure and death. POIKTMP is a rare, multi-organ fibrosing disease which is associated with mutations of the human FAM111B gene. FAM111B gene codes for a protein whose function is not well characterized. Therefore, elucidating the mechanism of FAM111B or its mutations in POIKTMP is beneficial to understanding the complexities surrounding this multisystemic fibrosing disease. The study sought to understand the pathogenesis of fibrosis, its role in POIKTMP and its causative gene mutation: FAM111B Y621D. First, Sanger sequencing was used to confirm the presence of the FAM111B Y621D mutation using DNA isolated and amplified from post-mortem FFPE tissues of a POIKTMP patient first described with the disease in South African Following that, qRT-PCR was employed to assess gene expression changes between the patient and the familial control. The RT2 Profiler Human fibrosis PCR Array was then used to associate POIKTMP and 84 known fibrotic markers to propose a possible fibrotic pathway associated with POIKTMP disease using mRNA from the lung and skin POIKTMP patient tissues. Gene-set enrichment analysis (GSEA) using Enrichr, a computational GSEA tool, was used to predict enrichment analysis between the identified upregulated fibrosis markers and the FAM111B gene. Finally, Immunohistochemistry was used to identify cellular and sub-cellular protein distribution of FAM111B and other fibroproliferative markers of interest to annotate pathological changes. The results from this study validated the FAM111B Y621D mutation in the affected tissues. Next, FAM111B mRNA was shown to be downregulated in the lungs and skeletal muscle tissues of the POIKTMP patient. The human fibrosis PCR array experiments identified eight upregulated fibrotic markers: MMP3, MMP13, PDGFA, ITGB-1, THBS-2, COL3A1, TGFβ3, and CCN2 in the patient lungs and skin tissues, which were validated by qRT-PCR. Furthermore, these genes with FAM111B form a gene-list that was used in interrogating various gene-set libraries in the gene-set enrichment analysis. FAM111B was enriched in some gene-set libraries within the Diseases/Drugs and Cell type categories. The GSEA terms enriched within these libraries are the pathways associated with SARS-COVID-19 perturbations and cell/tissue types related to the small intestine, breast, oesophagus, thyroid, smooth muscle and stromal cells of some of these organs. Lastly, immunohistochemistry results corroborated this study's mRNA expression analysis by showing that FAM111B was more highly expressed in the skin than in the lung patient. TGF-β1 and Ki-67 markers were 12 assessed from protein expression, which resulted in higher expression in the POIKTMP patient skin tissue than in the lungs. Altogether, our data suggest that FAM111B and mutations in this gene play a pivotal role in POIKTMP and other fibrosing organ diseases, representing a potential disease biomarker and possible therapeutic target in POIKTMP and other fibrotic disorders.